ONLINE SELLING: EFFICACY, SELLERS’ MARKETING STRATEGIES, AND CONSUMERS’ BUYING BEHAVIOR - Javier, Jayram B. (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
The advent of online selling in Capiz has revolutionized the operations of local businesses by offering a platform to exhibit products to the global market, thereby promoting economic development in the province. This research study sought to determine the effectiveness of online selling, the marketing methods employed by sellers, and the buying behavior of consumers. This study used a descriptive correlational research design to gather information. The study included a total of 110 online consumers and 15 online sellers in the province of Capiz. The participants were selected using purposive sampling. A researcher-made survey questionnaire and interview guide were used in this study. The data were analyzed and interpreted using the percentage, mean, and Pearson r. The findings of the study showed that the level of efficacy of online selling as a whole and in terms of accessibility, convenience, price, product selection, and customer reviews was very effective. Moreover, the level of the sellers’ marketing strategies was very effective. However, the overall level of consumers’ buying behavior was moderately good. Consequently, when categorized according to socio-demographic profile namely, age, sex, civil status, highest educational attainment, and monthly income, consumers’ buying behavior was average. Lastly, a low relationship but significant was observed between the efficacy of online selling and consumers' buying behavior.